2018
DOI: 10.1051/matecconf/201821103011
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of cutting tool vibration and surface roughness in hard turning of AISI52100 steel

Abstract: The changing behavior of vibration signals with varying cutting parameters (cutting speed, feed rate and depth of cut) for turning hardened AISI52100 steel has been studied and reported. The vibration response of cutting tool in all three mutually perpendicular directions, namely, in feed Vx, radial Vy and, tangential Vz directions have been captured by mounting piezoelectric tri-axial accelerometer close to the cutting tool. Experiments are planned and conducted as per Central composite rotatable design of Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Using the aforementioned analytic solving procedure and the relations ( 27) and ( 28) we calculate the amplitude and frequency of vibration, according to (13)…”
Section: Discussion and Results Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Using the aforementioned analytic solving procedure and the relations ( 27) and ( 28) we calculate the amplitude and frequency of vibration, according to (13)…”
Section: Discussion and Results Analysismentioning
confidence: 99%
“…As the cutting force depends on the feed value and the velocity it is expected that these parameters have an influence on the vibration property of the system and roughness of the cutting surface. Using the values given in Table 1 and relations (13) and (18), the amplitude and frequency of vibration of the workpiece-cutting tool system are calculated and shown in Table 2.…”
Section: Discussion and Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Cutting velocity and depth of cut have a negligible effect on surface roughness. Nitin Ambhore et al [4] conducted experiments to investigate the effect of cutting speed, tool amount and cutting depth on surface roughness when turning AISI 52100 steel with a cutting piece marked CNMG120408-MF5. The testing process was conducted by RSM method based on CCD test matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results have shown that induced vibration has significant impact on surface roughness which can be used to control the finished surface of a work pieces during mass production. The changing behaviour of vibration signals with varying cutting parameters (cutting speed, feed rate and depth of cut) for turning hardened AISI52100 steel has been studied in [9]. Experiments are planned and conducted as per Central composite rotatable design of Surface response methodology.…”
Section: Introductionmentioning
confidence: 99%